Integrating Evidence of the Traditional Chinese Medicine Collateral Disease Theory in Prevention and Treatment of Cardiovascular Continuum - Iokfai Cheang; Shengen Liao; Qingqing Zhu; Gehui Ni; Cong Wei; Cong Wei; Zhenhua Jia; Zhenhua Jia; Yiling Wu; Yiling Wu; Xinli Li (Frontiers Media S.A., 2022)
Cardiovascular disease has become a major public health problem. The concept of "cardiovascular continuum" refers to the continuous process from the risk factors that lead to arteriosclerosis, vulnerable plaque rupture, myocardial infarction, arrhythmia, heart failure, and death. These characteristics of etiology and progressive development coincide with the idea of "preventing disease" in traditional Chinese medicine (TCM), which corresponds to the process of systemic intervention. With the update of the understanding via translational medicine, this article reviews the current evidence of the TCM collateral disease theory set prescriptions in both mechanical and clinical aspects, which could lead to the development of new therapeutic strategies for prevention and treatment.